Late chronotype is linked to greater cortical thickness in the left fusiform and entorhinal gyri. Issue 10 (3rd October 2022) - Zareba, Michal Rafal; Fafrowicz, Magdalena; Marek, Tadeusz; Beldzik, Ewa; Oginska, Halszka; Domagalik, Aleksandra
ABSTRACT: Humans can be classified as early, intermediate and late chronotypes based on their preferred sleep and wakefulness patterns. Eveningness is associated with increased risk of developing several psychiatric conditions, such as major depressive and addictive disorders, however, the anatomical basis of chronotype distinctions, which might predispose to the above conditions, remains largely unexplored. Using magnetic resonance imaging data from 113 healthy young adults (71 females), we aimed to correlate individual chronotype scores with cortical thickness, as well as subcortical and cerebellar grey matter volume. The results revealed one cluster located in the left fusiform and entorhinal gyri showing increased cortical thickness with increasing preference for eveningness. These structures are well positioned to mediate well-established chronotype differences in affective processing, i.e. increased negative affect in late chronotypes. Furthermore, in line with the earlier findings, we found no differences in subcortical and cerebellar grey matter volume. Thus, our study confirms that circadian preference is associated with specific structural cortical substrates and provides a potential anatomical basis for differential affective functioning in morning- and evening-oriented individuals, bridging the gap between brain structure and function.